2017
DOI: 10.1371/journal.pone.0178030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of histatin-1 peptide on human corneal epithelial cells

Abstract: PurposeOcular surface and corneal epithelial wounds are common and potentially debilitating problems. Ideal treatments for these injuries would promote epithelial healing without inflammation, infection and scarring. In addition the best treatments would be cost-efficient, effective, non-toxic and easily applied. Histatin-1 peptides have been shown to be safe and effective enhancers of epithelial wound healing in other model systems. We sought to determine whether histatin-1 peptides could enhance human cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 23 publications
5
39
0
Order By: Relevance
“…However, due to the large variety of biomaterials, there is still an apparent great need for broadly applicable approaches to promote cell spreading on biomaterials. Previously, we and others showed that Hst1 promoted adhesion, spreading, and migration of various epithelial cells from different origins, such as mucosa , gingiva , cornea , and skin , endothelial cells , and osteogenic cells . All together, these findings underline a non‐cell type‐specific character of Hst1 rendering a promising application potential for tissue engineering purposes.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…However, due to the large variety of biomaterials, there is still an apparent great need for broadly applicable approaches to promote cell spreading on biomaterials. Previously, we and others showed that Hst1 promoted adhesion, spreading, and migration of various epithelial cells from different origins, such as mucosa , gingiva , cornea , and skin , endothelial cells , and osteogenic cells . All together, these findings underline a non‐cell type‐specific character of Hst1 rendering a promising application potential for tissue engineering purposes.…”
Section: Resultssupporting
confidence: 52%
“…A promising candidate cell‐targeting agent to promote cell–substrate interactions is histatin‐1 (Hst1), a member of a large histidine‐rich salivary peptide family. Our previous findings show that Hst1 can significantly promote the attachment, spreading, and migration of various cell types including epithelial, endothelial, and osteogenic cells . Our recent data confirm that Hst1 can promote the spreading of osteogenic cells on both bio‐inert glass and titanium surface , which suggests a promising application potential of Hst1 in the cell‐based bone tissue engineering.…”
supporting
confidence: 65%
“…Comparable cell activating effects for Hst1 and Hst2 have also been found on endothelial cells, fibroblasts and osteogenic cells [5,12]. Hst1 also stimulates cell metabolic activity [13] and maintains cell viability under various adverse conditions, such as the presence of zoledronic acid [14] or ultraviolet radiation [15]. Interestingly, Hst1 and Hst2 are internalized in epithelial cells [2,7] in contrast to the D-enantiomer of Hst2 (D-Hst2), which can not promote the migration of epithelial cells and neither is internalized by the cells [3].…”
Section: Introductionmentioning
confidence: 88%
“…From the above described results it may be deducted that the absence of amino sequences 1-11 in Hst2 and 23-38 in Hst5 (compared to Hst1) dramatically compromised their uptake rates. Consequently, we assessed the uptake dynamics and subcellular targets of truncated variants, F-Hst1 1-11 , F-Hst1 [12][13][14][15][16][17][18][19][20][21][22] and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] to explore their role in the cellular uptake of Hst1, Hst2 and Hst5. CLSM images revealed that the uptake of the truncated variants F-Hst1 1-11 , F-Hst1 12-22 and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] was much lower than that of the whole molecule F-Hst1 ( Figure 7A-D).…”
Section: Uptake Dynamics and Subcellular Target Of Truncated F-hsts mentioning
confidence: 99%
See 1 more Smart Citation